Integrating Remote Sensing Techniques and Geographic Information Systems to Assess the Environmental Impacts of Urban Sprawl on Agricultural Lands: A Case Study from Suq Al-Shuyoukh City, South of Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
The current study aims to determine the size, type, direction and causes of urban encroachment on agricultural lands as well as its environmental impact. The remote sensing and geographic information systems techniques are integrated to determine the extent of horizontal urban growth in Suq Al-Shuyoukh City for two periods (3/2003 and 4/2020). The normalized difference vegetation index (NDVI), accumulated normalized difference index (NDBI) and normalized difference water index (NDWI) are used. A supervised classification technique using ArcGIS software is used to map the different land use land cover (LULC) classes. The LULC map indicates a significant increase in urban (+10%) areas and arid lands (+6%), and a significant decrease in agricultural land (-17%). The city underwent major urban expansion towards north and northeast. The chaotic urban sprawl in study area can be classified as irregular urban sprawl. The population increase (+2.31%) has a role in urban expansion. The environmental impacts are rising temperatures, desertification and an increased frequency of dust storms.
Keywords: geomorphological units, encroachment, Man Made, supervised classification, desertification